Effect of industry-specialist auditors, auditor’s tenure, and auditor’s size on the quality of disclosure in the UAE Stock Exchange - Mohaisen, Hussein Ali; Saedi, Rahman; Ali, Khalid Sabah (Heritage and Sustainable Development, 2024)
Having access to real-world information and accurate data is a key factor in improving auditor performance, which in turn impacts business performance and decision-making. Consequently, this research aims to determine how financial institutions' levels of experience impact the accuracy of the information they disclose. The present statistical population consists of all 127 businesses listed on the United Arab Emirates Stock Exchange. This type of research is categorized as applied studies in relation to the research methods used in the UAE stock market. Using a systematic deletion procedure, 46 companies were chosen based on the study's inclusion criteria. The findings revealed that in the UAE, the quality of financial information disclosure for companies listed on the UAE stock exchange is significantly affected by the auditor's decision-making experience, the duration of their job, and the size of the auditor.